Against Single Stories of ‘Left Behind’ and ‘Triple Win’: On Agricultural Care Chains and the Permanent Subsistence Crisis - Bolokan, Dina (Frontiers in Sociology, 2021)
The single story of Moldova as the “country without parents” is unsettling. While it is true that villages in Moldova, as in other post-Soviet regions and global peripheries, are affected by intensive outmigration and labor mobility, the image is incomplete. In this article, I propose a different telling of this story: one that looks at and challenges the structural power relations visible in people’s lives in rural Moldova. It is a telling that points to the overall subsistence crisis in Europe and the relationship between neocolonial entanglements and agricultural care chains. As such, this article aims to bring together reflections on labor migration, well-being in rural areas and the global care economy while seeking to decolonize subsistence production and the abolition of the international division of (re)productive labor.